An approach to the stochastic calculus in the non-Gaussian case. (1995) - Dorogovtsev, Andrey A.
Abstract : We introduce and study a class of operators of stochastic differentiation and integration for non-Gaussian processes. As an application, we establish an analog of the Itô formula.